2018
DOI: 10.1080/19336918.2018.1486142
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits LPS-induced macrophage migration by suppressing the iNOS/FAK/paxillin pathway and modulating the cytoskeleton

Abstract: The natural flavonoid quercetin has antioxidant, anti-inflammatory, and anticancer effects. We investigated the effect of quercetin on lipopolysaccharide (LPS)-induced macrophage migration. Quercetin significantly attenuated LPS-induced inducible nitric oxide synthase (iNOS)-derived nitric oxide (NO) production in RAW264.7 cells without affecting their viability. Additionally, quercetin altered the cell size and induced an elongated morphology and enlarged the vacuoles and concentrated nuclei. Quercetin signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
5
30
0
Order By: Relevance
“…Firstly, these processes require actin cytoskeleton reorganization, which leads to several cellular responses, such as migration. Different compounds are present in the BB extracts obtained by Cui et al (2019), and among them, quercetin, one of the most common flavonoids, was recently shown to interfere in macrophage migration processes induced by LPS. It significantly disrupted the F-actin cytoskeleton structure and promoted changes in the size and shape of the macrophages, affecting the formation of filopodia or lamellipodia, which are supported by actin filaments and associated proteins [62].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, these processes require actin cytoskeleton reorganization, which leads to several cellular responses, such as migration. Different compounds are present in the BB extracts obtained by Cui et al (2019), and among them, quercetin, one of the most common flavonoids, was recently shown to interfere in macrophage migration processes induced by LPS. It significantly disrupted the F-actin cytoskeleton structure and promoted changes in the size and shape of the macrophages, affecting the formation of filopodia or lamellipodia, which are supported by actin filaments and associated proteins [62].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin (QCT), a natural flavonoid which is commonly found in numerous fruits and vegetables, is an indispensable part of the diet. QCT comes into the focus of medicinal interest because of its extensive pharmacological effects, such as anti-cancer, anti-viral, anti-oxidant, anti-inflammatory and anti-senescence effects [10] , [11] , [12] , [13] , [14] . A previous study reported that QCT could selectively kill senescent cells and enhance lifespan in old mice [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The active compounds were chosen based on the previously study and literature mining. As acacetin, kaempferol, quercetin are predicted as active compounds by in silico study, we previously reported that quercetin inhibited LPS induced macrophage migration by inhibiting iNOS/FAK/Paxillin pathway ( Cui et al, 2019 ). Therefore, acacetin, kaempferol are selected for the further validation.…”
Section: Resultsmentioning
confidence: 99%
“…FAK binds to proteins containing the Src sequence to form FAK/Src complex. Then FAK/Src complex recruits downstream proteins, such as paxillin to participate in the regulation of cell cycle, adhesion, and metastasis ( Cui et al, 2019 ). Our previous study confirmed that quercetin inhibited the iNOS/FAK-paxillin pathway to limit LPS-induced macrophages migration ( Cui et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation